PENGARUH PENGGUNAAN SISTEM PEMBAYARAN NON TUNAI (APMK DAN UANG ELEKTRONIK) TERHADAP JUMLAH UANG BEREDAR (M1) DI INDONESIA - Arthur, Eduardus (Jurnal Ilmiah Mahasiswa FEB, 2016)
Bank Indonesia as monetary authorities in Indonesia has a task for organize and maintain smooth and overseeing the payment system, either in cash payment system and non-cash payment system. As technology advances, the payment system that allows people continue to experience growth, one of them is Through Card and electronic money. The presence of non-cash payment system will have an impact on demand for money and money supply in society. This study aims to see how short-term and long-term effect of non-cash payment system on money supply in Indonesia.In this study, non-cash payment system represented by Through Card and electronic money. This study use quantitative research methods and using Error Correction Model (ECM) with time series data. The result showed that in the short-term, variable transaction value of credit card and transaction value of electronic money effect on money supply (M1) in Indonesia, whereas in the long-term, variable transaction value of ATM+debit card and transaction value of credit card effect on money supply (M1) in Indonesia.Â Keywords: Non-cash Payment System, Though Card, Electronic Money, Money Supply (M1), Error Correction Model (ECM).